DEPENDENCE OF THE SPECIFICITY OF INTERNET TEXT UNDERSTANDING ON DEVELOPMENT OF THINKING-SPEECH ABILITIES - Akimova, Nataliia (PSYCHOLOGICAL JOURNAL, 2019)
The article presents the empirical study of the influence of thinking and speech development on the results of Internet texts understanding. Different theoretical methods and techniques were used for this purpose: deductive and inductive methods, analysis and synthesis, generalization, systematization. The following empirical methods were used for this purpose: experiment (semantic and receptive), the method of semantic and pragmatic interpretations, content analysis, and the subjective scaling procedure. The following mathematical methods were used: primary statistics, checks on the data distribution normality, the statistical output, taking into account statistical mode and variation. Some interpretive methods based on specific principles of the systemic, activity, cognitive and organizational approaches were used also. The empirical research involved 716 respondents from different regions of Ukraine, ant it revealed that thinking and speech development influences most significantly on the understanding process at the reception stage; here users' activities are guided and their expectation accuracy is determined. The results achieved by readers with highly developed thinking-speech abilities are better by 18-22% at this stage. At the stage of interpretation, the adequacy and completeness of Internet text interpretations are improved by almost 10% with the experience accumulation. At the stage of emotional identification, there is a direct correlation between the understanding adequacy and thinking-speech development, but it is much weaker (only 6%). Instead, there is a clear dependence between emotional attitude awareness and thinking-speech development at this stage, this correlation is 17%. The users with highly developed thinking-speech abilities evaluate Internet texts more homogeneously, they are better and more consistently understand their own attitudes to Internet texts. However, like inexperienced readers, they underestimate the complexity of Internet texts in more than half of the cases, they are also inclined to divide texts on approved and criticised.